A Survey of the Practice Status Quo of Ultrasound-Guided ECC Tip Location for Neonatal Patients in 31 Provinces of China - Liu, Xuexiu; Tao, Xiaojun; Xu, Ye; Zhang, Xianhong; Wu, Liping (Frontiers in Pediatrics, 2022)
Abstract Objective: To investigate the status quo of implementing ultrasound (US)-guided peripherally inserted central catheter (PICC) tip placement for neonatal patients in 31 provinces. Methods: The convenience sampling method was used to investigate the nursing managers and PICC (or intravenous therapy) nurses of 91 hospitals in 31 provinces from October 29 to November 10, 2021. Results: The survey involved a total of 182 medical staff, including 91 managers and 91 nurses, and 91 institutions, including 22 children's hospitals, 49 general hospitals and 21 maternal and child health care hospitals. Sixteen hospitals (17.6%) carried out US-guided PICC for neonatal patients; 176 subjects (96.7%) of the 91 hospitals had known about or heard of the technology of US-guided PICC. The low awareness of operators of the tip positioning of PICC catheters in children under ultrasound guidance (OR = 2.690, 95% CI = 1.163-6.221), limited conditions in existing wards (OR = 2.953, 95% CI = 1.285-6.790), and insufficient funds (OR = 2.836, 95% CI = 1.149-7.004) were the independent risk factors responsible for the failure to carry out ultrasonic-guided positioning of PICC tips in newborns. Conclusion: The popularity of neonatal US-guided PICC placement was seriously hindered by factors such as a low awareness rate of the project, the low qualification certification rate of the nursing staff, a flawed performance allocation system, and the lack of a professional team, among other factors.